2019
DOI: 10.5152/iao.2019.6550
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Round Window Operations for the Treatment of Superior Semicircular Canal Dehiscence

Abstract: Journal of International Advanced Otology requires and encourages the authors and the individuals involved in the evaluation process of submitted manuscripts to disclose any existing or potential conflicts of interests, including financial, consultant, and institutional, that might lead to potential bias or a conflict of interest. Any financial grants or other support received for a submitted study from individuals or institutions should be disclosed to the Editorial Board. To disclose a potential conflict of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This hearing loss persisted despite a systemic treatment by corticosteroids and antibiotics, followed by a revision surgical procedure to remove the material used to reinforce the round window, and apply dexamethasone, to reduce the local inflammatory phenomena. RWR remains a minimally invasive alternative 8 and may be considered in patients at high anesthetic or surgical risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hearing loss persisted despite a systemic treatment by corticosteroids and antibiotics, followed by a revision surgical procedure to remove the material used to reinforce the round window, and apply dexamethasone, to reduce the local inflammatory phenomena. RWR remains a minimally invasive alternative 8 and may be considered in patients at high anesthetic or surgical risk.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Kartush et al introduced the window reinforcement technique via the external ear canal to suppress the effect of the third window, described in Silverstein et al 7 Their results were deemed satisfactory in 4 out of 6 cases treated, but subsequent studies carried out with this technique yielded variable results. 8 …”
Section: Introductionmentioning
confidence: 99%
“…88,89 Ahmed et al ., in 2019, reviewed the available evidence on round window obliteration; they concluded that the evidence is scant and that this procedure is unlikely to replace the better-established techniques of superior semicircular canal resurfacing or obliterating. 89…”
Section: Treatment Optionsmentioning
confidence: 99%
“…The even more recently introduced obliteration of the round window (which aims to block the natural second window, the round window), 87 despite the initial enthusiasm associated with its technical simplicity (it can be performed as a day-case procedure), has not shown adequate control of the patients' symptoms. 88,89 Ahmed et al, in 2019, reviewed the available evidence on round window obliteration; they concluded that the evidence is scant and that this procedure is unlikely to replace the better-established techniques of superior semicircular canal resurfacing or obliterating. 89 An early review paper published in 2009 on the efficacy and complications of surgical approaches showed only studies with short-term follow up, and an absence of standardised assessment and documentation methods.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…However, it is worth mentioning, even briefly, the alternative of round window obliteration as a surgical method to improve the SSCD related symptoms. Despite the initial results, latest studies have shown poor control of the patients' symptoms questioning the significance of such technique (22,23).…”
Section: Symptom Control and Realistic Expectationsmentioning
confidence: 99%